PGSE diffusion studies on chelating phosphine complexes of ruthenium(II). Solvent dependence and ion pairing - Kumar, P; Pregosin, P; Goicoechea, J; Whittlesey, M (2003)
POSE 1H and 19F diffusion data, D values, and 1H 19F HOESY NMR spectra for a series of [RuCl(p-cymene)(BINAP)]X salts, 2a-f, have been recorded in CD 2Cl 2 (X = BF 4- (2a), CF 3 SO 3- (2b), BArF - (2c), PF 6-(2d), SbF 6- (2e), Cl - (2f)). The solvent dependence of the D values for 2a - c in methanol, chloroform, dichloromethane, and acetone and the resulting ion-pairing effects are discussed. On the basis of HOESY data, it is suggested that small anions in chloroform solution approach the ruthenium atom from the side of the molecule remote from the chloride and slightly below the complexed arene. PGSE diffusion data for the Ru-aqua complexes [Ru(H 2O) 3(CO)(dppe)]X 2 (X = BF 4- (3a), CF 3SO 3- (3b), SbF 6 (3c), N(O 2SCF 3) 2- (3d)) are reported. The observed D values for 3a-d partially reflect hydrogen bonding from complexed water to the anions. © 2003 American Chemical Society.